THE MEANING OF CULTURAL HERITAGE: CIKENDI SPRING PROTECTION FORTRESS - Razaq, Yasmin Nur; Handayani, Sri (Journal of Development and Integrated Engineering, 2023)
The Cikendi Spring Protection Building is listed in the list of Cultural Heritage sites. From a historical perspective, this building holds a number of stories and memories for the city of Bandung. However, it seems as if Cikendi's struggle is being ignored, the community is less concerned about the existence of the Cultural Heritage Building. In fact, if examined more deeply, the Cultural Heritage Building has so many meanings to be explored. The purpose of this research is to make us aware that the Cikendi Cultural Heritage Site is not just a Dutch heritage building, but it holds history and real evidence that springs are useful for us today, maybe tomorrow, or in the future. This research is qualitative in nature, where the data is obtained based on existing theoretical studies. The existence of the Cikendi Spring Protection Fort is a silent witness to the struggles of our ancestors as well as a tangible result of the work of civilization in the past. The success of our ancestors in utilizing the surrounding environment so that the benefits of Cikendi Springs can still be felt today